Strategi Pengelolaan Sampah Plastik di Kampung Wisata Arborek Raja Ampat - Macap, Faridz Chalid; Abu, Nur; Dwangga, Mierta; Marasabessy, Umar (Universitas Tanjungpura, 2025)
This study was conducted on the island of Arborek using data determination techniques with observations and questionnaires shared with respondents. The data obtained was then analyzed using SWOT analysis to obtain a plastic waste management strategy. The results of the study showed that the management of plastic waste on the island of Arborek was carried out by the Non-Governmental Organization